A reflection on research in Mathematics Education and Education of the Deaf - Soares, Maria; Sales, Elielson (Educação Matemática Debate, 2018)
This article is part of a master’s dissertation held at the Institute of Mathematical and Scientific Education (IEMCI) of the Federal University of Pará (UFPA), and aims to discuss strictu sensu research on Mathematics Education and Education of the Deaf. It is a qualitative, state-of-the-art study that analyzes 31 researches that fit into the thematic axes teacher training, curriculum adaptation, Mathematics Education and communication, and teaching and learning. The researches were carried out in four Brazilian regions with greater representativeness in the southeast and northern Brazil, being in the latter concentrated in the IEMCI / UFPA. The study points to a growth of research in the scope of postgraduate studies and highlights the reality of education for inclusive education, highlighting the need for practicing Libras in Mathematics teaching, bilingualism in teaching the deaf, adapting didactic materials with visual instruments, and the training of educators for inclusion.